Magnesium sulfate infusion for acute asthma in the emergency department - Jose Enrique Irazuzta; Nicolas Chiriboga (Jornal de Pediatria)
Abstract Objectives: To describe the role of intravenous magnesium sulfate (MgSO4) as therapy for acute severe asthma in the pediatric emergency department (ED). Source: Publications were searched in the PubMed and Cochrane databases using the following keywords: magnesium AND asthma AND children AND clinical trial. A total of 53 publications were retrieved using this criteria. References of relevant articles were also screened. The authors included the summary of relevant publications where intravenous magnesium sulfate was studied in children (age <18 years) with acute asthma. The NAEPP and Global Initiative for Asthma expert panel guidelines were also reviewed. Summary of the data: There is a large variability in the ED practices on the intravenous administration of MgSO4 for severe asthma. The pharmacokinetics of MgSO4 is often not taken into account with a consequent impact in its pharmacodynamics properties. The cumulative evidence points to the effectiveness of intravenous MgSO4 in preventing hospitalization, if utilized in a timely manner and at an appropriate dosage (50-75 mg/kg). For every five children treated in the ED, one hospital admission could be prevented. Another administration modality is a high-dose continuous magnesium sulfate infusion (HDMI) as 50 mg/kg/h/4 h (200 mg/kg/4 h). The early utilization of HDMI for non-infectious mediated asthma may be superior to a MgSO4 bolus in avoiding admissions and expediting discharges from the ED. HDMI appears to be cost-effective if applied early to a selected population. Intravenous MgSO4 has a similar safety profile than other asthma therapies. Conclusions: Treatment with intravenous MgSO4 reduces the odds of hospital admissions. The use of intravenous MgSO4 in the emergency room was not associated with significant side effects or harm. The authors emphasize the role of MgSO4 as an adjunctive therapy, while corticosteroids and beta agonist remain the primary acute therapeutic agents.